How Indonesia Became a World Leader in Islamic Education: A Historical Sociology of a Great Transformation - Hefner, Robert W. (UIII Press, 2022)
Over the past twenty years, educators around the world have worked to devise curricula to educate students about how to live together as citizens in diverse societies. In Muslim educational circles, this task has been made additionally challenging by jurisprudential legacies from classical times that make strict and hierarchical distinctions between Muslims and non-Muslims. This essay presents a historical sociology of educational reform in Islamic schools in Indonesia with regards to education about citizenship and nation. This study shows that the late-nineteenth century ascendance of madrasa-like institutions across the Indonesian archipelago meant that the widespread adoption of a more-or-less standardized fiqh-focused curriculum (like that long common in Middle Eastern and South Asian madrasas) coincided with two other developments: the rise of Indonesian nationalism, with an emphasis on multi-religious citizenship, and the spread of modernist-style “Islamic schools” (sekolah Islam) with a broad-based academic curriculum. The coincidence of these three currents ensured that here in Indonesia Islamic schooling adopted a general curriculum emphasizing the sciences of the world in addition to Islamic sciences more readily than in many other Muslim lands. In a manner that anticipated a shift recently seen in other Muslim-majority countries, Islamic educators did so while also prioritizing Islamic ideals of the public good (maslahat) and purpose-driven (maqasid) ethics over legal formalism, and rallying to the ideal of Indonesian traditions of multi-religious citizenship. In all these regards, Islamic higher education contributed greatly to contemporary Indonesia’s cultural and democratic reform.